Ambliopía y estrabismo en paciente masculino de 5 años. - Medina Moran, Mariuxi Marife (2022)
When there is no alignment in the gaze, the patient presents a picture of strabismus, this situation implies discomfort in those who suffer from it. It is generally associated with amblyopia, which manifests itself as loss of visual acuity in one eye. Strabismus is usually detected in the first years of life, presenting various types in relation to the etiology, age of detection and adequate treatment. In the present clinical case we treat a 5-YEAR-OLD MALE PATIENT WITH AMBLYOPIA AND STRABISMUS, who underwent the respective tests. And it was determined that the strabismus present in the minor can be treated through the implementation of aerial lenses combined with an ocular occlusion therapy to improve the symptoms of amblyopia.